Correction and Rectification of Light Fields - Deng, Ke; Wang, Lifeng; Lin, Zhouchen; Feng, Tao; Deng, Zhidong; Guo, Baining (Elsevier, 2003)
The light field is a well known image-based rendering technology. The traditional way to capture a light field is to move a camera on a plane and take images at every gird points. However, due to device defects it is hard to ensure that the captured light field is ideal. For example, the camera’s imaging plane is not on the image plane of the light field and the camera is not in the right position. To solve this problem we propose a correction and rectification framework that uses only four images. This framework involves un-distortion, feature point detection, homography computation to correct the orientation of the camera, and positional error correction. It is the first to take positional error into consideration. Our experiments show that our method is effective.